Evaluation and comparison of functional and esthetic outcomes of pectoralis major myocutaneous flap with or without removal of sternocleidomastoid muscle following neck dissection in patients being operated for oral squamous cell carcinoma - Dhrumil Nitish Sarkar; Nitin Bhola; Anchal Agrawal (Oral Oncology Reports)
India comprising the burden of oral squamous cell carcinoma which grow locally and then spreads to the cervical lymph nodes. Neck dissection is a beneficial procedure for addressing metastases in the neck arising from head and neck cancers. This surgical technique aims to remove lymph nodes on one side of the neck where cancer cells may have spread. However, this procedure can significantly impact a patient's appearance and cause distortion in the cervical area, particularly when it involves the removal of the sternocleidomastoid muscle, leading to a flattening effect in the lateral neck area. Reconstructing tissue defects following extensive surgeries in the head and neck region presents a distinct challenge for surgeons. They have the option to use either pedicled or free tissue transfer for this purpose. We compared and evaluated functional and esthetics outcomes of pectoralis major myocutaneous flap with or without removal of sternocleidomastoid muscle following neck dissection. We concluded that lack of notable distinction between the MRND type II and III groups. Both groups exhibited restricted range of motion in flexion, abduction, and external rotation. Notably, there was a significant impact on neck circumference, while shoulder functionality demonstrated gradual improvement over time. Interestingly, no substantial variances were observed between the groups in terms of drainage and wound healing. The quality of life reported by participants was generally favorable, with composite scores, social-emotional sub-scores, and average physical function aligning with acceptable standards. It's important to note that achieving a more substantial sample size is imperative to obtain results of greater significance and reliability.